Pengaruh Daya Tarik Iklan Dan Brand Ambassador Song Joong Ki Terhadap Brand Image Scarlett Whitening - Jonathan Jonathan; George Nicholas Huwae George Nicholas Huwae (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
The purpose of this research is to verify the impacts of advertising appeal and Song Joong Ki as brand ambassador for Scarlett Whitening’s brand image. The method that used in this research is quantitative, populated by 519 UKSW FTI faculty’s female college student. The sample selection is using Purposive Sampling technique comprising of 100 samples as respondents that are eligible to be used in this research. The sampling technique used was is spreading the questionnaire and used multiple regression as an analysis technique. Research results found that : (1) The advertising appeal gives positive effect to Scarlett Whitening’s brand image with score t-count in the amount of 3.146 > score t-table 1.984 and the level of significance is 0.002. (2) Song Joong Ki as brand ambassador gives positive effect to Scarlett Whitening’s brand image with score t-count in the amount of 5,781> score t-table 1.984 and the level of significance is 0.000. (3) Advertising appeal and Song Joong Ki brand ambassador simultaneously gives positive effects to Scarlett Whitening’s brand image with F count score in the amount of 27.472 > F table score 2.70 and the level of significance 0.000. (4) The amount of influence from advertising appeal and Song Joong Ki brand ambassador to Scarlett Whitening’s brand image (R2) is 36.2%.